2021
DOI: 10.1002/adsc.202100009
|View full text |Cite
|
Sign up to set email alerts
|

Haloalkenyl Imidoyl Halides as Multifacial Substrates in the Stereoselective Synthesis of N‐Alkenyl Compounds

Abstract: N‐Alkenyl compounds are versatile synthetic building blocks and their stereoselective transformations are key processes in the synthesis of many prominent classes of natural products, pharmaceuticals, and agrochemicals. However, a large structural variety of known N‐alkenyl compounds and their diverse reactivity have so far precluded the development of a general method for their stereoselective synthesis. Herein we present an aluminum halide‐mediated, highly stereoselective, efficient and scalable transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…We have recently reported that transannulation efficiently proceeds for N-fluoroalkylated triazoles, [16][17][18][19] which allowed to overcome the limitation of the presence of sulfonyl group. Moreover, a ring cleavage of electron-deficient triazoles in the presence of Brønsted and Lewis acids, proceeding via a vinyl cation intermediate, was reported by our [20][21][22] and other 23 groups. However, the preparation of N-sulfonyl and N-fluoroalkyl triazoles requires multiple synthetic steps.…”
supporting
confidence: 54%
“…We have recently reported that transannulation efficiently proceeds for N-fluoroalkylated triazoles, [16][17][18][19] which allowed to overcome the limitation of the presence of sulfonyl group. Moreover, a ring cleavage of electron-deficient triazoles in the presence of Brønsted and Lewis acids, proceeding via a vinyl cation intermediate, was reported by our [20][21][22] and other 23 groups. However, the preparation of N-sulfonyl and N-fluoroalkyl triazoles requires multiple synthetic steps.…”
supporting
confidence: 54%
“…9−13 Recently, we have showcased a new type of reactivity specific to N-fluoroalkyl-1,2,3-triazoles in the presence of strong Brønsted 14 or Lewis acids. 15 In comparison to rhodium-catalyzed reactions utilizing heating-induced ring opening and rhodium carbene formation, acid-mediated transformations proceed via protonation or coordination of N(1) on the triazole ring leading to diazonium salt 5, which upon nitrogen elimination forms vinyl cation 6. Delivering the (pseudo)halogen takes place from the same side as the fluoroalkyl-bound nitrogen, making the reaction highly stereoselective with respect to the Z stereoisomer (Figure 1B).…”
mentioning
confidence: 99%
“…B: Ligand-controlled stereoselective synthesis of β,β-diaryl-substituted enamides. pling reactions with retention of configuration on the double bond and served as valuable starting materials for the synthesis of functionalized β,β-disubstituted enamides (Scheme 1A) [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported a triflic acid-mediated reaction of N -fluoroalkyl-1,2,3-triazoles leading to ( Z )-β-enamido triflates [ 21 ] and Lewis acid-mediated reaction to ( Z )-β-enamido fluorides [ 22 ] and halovinyl imidoyl halides [ 23 ]. In addition, Li and co-workers extended the scope of accessible ( Z )-β-enamido triflates by denitrogenative reaction of N 1- H -1,2,3-triazoles in the presence of acyl halides and sodium triflate [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation